2019
DOI: 10.1186/s12874-019-0718-8
|View full text |Cite
|
Sign up to set email alerts
|

The judgement of biases included in the category “other bias” in Cochrane systematic reviews of interventions: a systematic survey

Abstract: Background Clinical decisions are made based on Cochrane reviews, but the implementation of results of evidence syntheses such as Cochrane reviews is problematic if the evidence is not prepared consistently. All systematic reviews should assess the risk of bias (RoB) in included studies, and in Cochrane reviews, this is done by using Cochrane RoB tool. However, the tool is not necessarily applied according to the instructions. In this study, we aimed to determine the types of bias and their corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 13 publications
1
25
0
Order By: Relevance
“…To reduce bias, we made independent assessments by two authors for each analyzed domain and sub-domain. Additionally, we included in the analysis only the first four domains of the Cochrane RoB tool, because instructions from the Cochrane Handbook for these four domains are better characterized compared to the remaining three domains [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To reduce bias, we made independent assessments by two authors for each analyzed domain and sub-domain. Additionally, we included in the analysis only the first four domains of the Cochrane RoB tool, because instructions from the Cochrane Handbook for these four domains are better characterized compared to the remaining three domains [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…However, RoB assessments made by authors of published systematic reviews should not be taken at the face value, as we have shown in multiple studies that RoB assessments in many Cochrane reviews were inadequate and inconsistent [7][8][9][10][11][12][13][14]. Due to the specificities of surgical trials, we hypothesized that assessments of surgical trials may be more accurate and more consistent, compared to RCTs of nonsurgical interventions.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is possible that the way the Cochrane authors judge RoB for sequence generation is highly variable. We have already proved this for RoB domains for allocation concealment [6], blinding of participants and personnel [7], incomplete outcome data [8], selective reporting [9], and other bias [10]. In that case, results presented in the study of Dechartres et al [5] or similar studies would not be based on consistent ratings of RoB in Cochrane reviews, and improvements shown for certain RoB domains could be misleading.…”
Section: Introductionmentioning
confidence: 99%
“…Cochrane risk of bias (RoB) tool, with seven dimensions, including sequence generation, allocation concealment, blinding of participants and personnel, blinding of outcome assessors, incomplete outcome data, selective outcome reporting and other potential threats to study validity will be used. We will assess RoB in line with instructions from the Cochrane Handbook for Systematic Reviews of Interventions22 to avoid mistakes review authors frequently make when conducting RoB assessments with this tool 23–27. For each study, we will create a RoB domain, which will have a RoB judgement for each domain (high, low or unclear risk) and an accompanying supporting comment to explain the RoB judgement.…”
Section: Methods and Analysismentioning
confidence: 99%